Without Avigad's Pictures—Is the Jerusalem Cardo Roman After All? (The Biblical archaeology review, 1977)
One of the most sensational finds of recent excavations in Jerusalem was Professor Nachman Avigad’s discovery of the ancient Cardo, the main north-south thoroughfare through the city.